2014
DOI: 10.1016/j.juro.2013.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Population Based Study of Predictors of Adverse Pathology among Candidates for Active Surveillance with Gleason 6 Prostate Cancer

Abstract: More than a third of men meeting the most stringent active surveillance criteria had adverse pathology at radical prostatectomy in this population based cohort. Active surveillance programs should consider prostate specific antigen density and extent of cancer on biopsy for patient selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
63
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 27 publications
9
63
1
2
Order By: Relevance
“…However, the latter population would be considered for radical treatment under current protocols, and the predictive utility of CCL/core therefore becomes limited. Similar to our present finding, Vellekoop et al [26] found that cancer length of >4 mm in patients with biopsy Gleason score 6 is predictive of worse outcome.…”
Section: Discussionsupporting
confidence: 92%
“…However, the latter population would be considered for radical treatment under current protocols, and the predictive utility of CCL/core therefore becomes limited. Similar to our present finding, Vellekoop et al [26] found that cancer length of >4 mm in patients with biopsy Gleason score 6 is predictive of worse outcome.…”
Section: Discussionsupporting
confidence: 92%
“…17,18 Indeed, most of the patients who underwent radical prostatectomy had upgrading or upstaging of their diagnosis when the prostatectomy specimen was examined. These data suggest that although active surveillance was commonly chosen, there was judicious use of definitive treatment for patients with an initial diagnosis of low-grade disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between PSAD and risk may vary across PCa risk levels and prostate volumes. 20,21 How to use PSAD when advising men on AS is still unclear.…”
mentioning
confidence: 99%